2017
DOI: 10.1364/oe.25.011778
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional reflectionless propagation in a non-ideal parity-time metasurface based on far field coupling

Abstract: We propose a scheme to achieve a controllable unidirectional reflectionless propagation at exceptional point (EP) in a non-ideal parity-time metasurface consisting of two silver ring resonators. The unidirectional reflectionless propagation can be manipulated by simply adjusting the angle of incident wave and the distance s between two silver rings based on the far field coupling. In addition, the angle of incident wave in a wide range of ∼25° is available to achieve the unidirectional reflectionless propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…2(b)) of the metasurface prove the totally suppressed and highly efficient retro-reflection (4% from left port and 90% from right port at 11.8 GHz), which provides a new perspective for designing an asymmetric optical system for wave manipulation. Unidirectional reflectionless propagation has also been achieved in a non-Hermitian metasurface consisting of two silver ring resonators coupled in the far field [33]. This metasurface shows a bilateral unidirectional reflectionless propagation that is insensitive to the incident angle (∼ 25 • ) and independent of polarizations.…”
Section: Unidirectional Propagationmentioning
confidence: 96%
See 1 more Smart Citation
“…2(b)) of the metasurface prove the totally suppressed and highly efficient retro-reflection (4% from left port and 90% from right port at 11.8 GHz), which provides a new perspective for designing an asymmetric optical system for wave manipulation. Unidirectional reflectionless propagation has also been achieved in a non-Hermitian metasurface consisting of two silver ring resonators coupled in the far field [33]. This metasurface shows a bilateral unidirectional reflectionless propagation that is insensitive to the incident angle (∼ 25 • ) and independent of polarizations.…”
Section: Unidirectional Propagationmentioning
confidence: 96%
“…A two-port metasurface can be described by a scattering matrix (Fig. 1(b)) that can be obtained by transmission matrix [33], impedance matrix [34], or admittance matrix [35], and sometimes combine with the coupled mode equations [36]. In metasurfaces satisfying PT symmetry, the scattering matrix of an active two-port system with balanced gain and loss has the form:…”
Section: Non-hermitian Metasurfacesmentioning
confidence: 99%
“…The multiple wave interference effect and near‐field coupling effect between layers make the few‐layer metasurface a powerful platform to tailor the reflection, transmission, and absorption of electromagnetic waves. By utilizing the multiple wave interference effect between the functional layers, Chen et al proposed a wide‐angle antireflection coating in the terahertz frequency range .…”
Section: Prominent Applications In Few‐layer Metasurfacesmentioning
confidence: 99%
“…So far, unidirectional reflectionlessnesses have been proposed in some non-Hermitian Hamiltonian systems with unbalanced gain and loss [21,22,23,24,25,26,27,28,29,30,31,32], such as passive (no gain) optical waveguide [21], large optical multilayer structure [22], two-layer slab [23], plasmonic waveguide [24,25,26,27], and metamaterial [28,29,30,31,32]. In 2013, Feng et al [21] experimentally demonstrated unidirectional reflectionlessness in PT symmetry optical waveguide system, where reflection from one port was distinctly diminished.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Bai et al [30] realized the unidirectional reflectionlessness based on near-field coupling of two stacked asymmetric nanostrips. Gu et al [31] and Bai et al [32] realized the polarization-insensitivity and polarization-switching unidirectional reflectionlessnesses in metamaterials based on far-field phase coupling between two resonators, respectively. However, the above studies [29,30,31,32] in metamaterials focused on single-band unidirectional reflectionlessnesses, the dual-band scheme was seldom mentioned.…”
Section: Introductionmentioning
confidence: 99%